ABOUT THE PHENOMENA OF TRADITIONALISM IN THE MODERN WORLDVIEW OF THE YAKUTS - Брагина, Дария (SWorldJournal, 2020)
At present, the relevance of the study of the traditional worldview of the peoples of Siberia and the North, including the Yakuts, is undoubted, and therefore arouses the interest of researchers. In this article, based on literary sources, field observat